Surface potential–based analysis of ferroelectric dual material gate all around (FE‐DMGAA) TFETs. (4th February 2020) - Mishra, Varun; Verma, Yogesh K.; Gupta, Santosh K.
Abstract: This paper presents an electrostatic potential–based analytical model of drain current for ferroelectric dual material gate all around tunnel field effect transistors (FE‐DMGAA‐TFETs). Analytical model is formulated to examine the device characteristics by combining the evanescent mode analysis (EMA) and Landau‐Khalatnikov equation. Ferroelectric material exhibits negative capacitance, which enhances the drain current by providing an amplification to the surface potential. The impact of varying the ferroelectric layer thickness on the device characteristics is studied. The accuracy of the model is evaluated by comparing it with the results obtained from numerical calculations and found to be in good accord. The ON current of the ferroelectric‐based TFETs is approximately 100 times the conventional DMGAA‐TFETs.